2017
DOI: 10.1038/srep41006
|View full text |Cite
|
Sign up to set email alerts
|

Examining trends in family planning among harder-to-reach women in Senegal 1992–2014

Abstract: Recent increases in family planning (FP) use have been reported among women of reproductive age in union (WRAU) in Senegal. However, trends have not been monitored among harder-to-reach groups (including adolescents, unmarried and rural poor women), key to understanding whether FP progress is equitable. We combined data from six Demographic and Health Surveys conducted in Senegal between 1992/93 and 2014. We examined FP trends over time among WRAU and subgroups, and trends in knowledge of FP and intention to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 26 publications
(40 reference statements)
4
26
0
1
Order By: Relevance
“…In Senegal, despite numerous health interventions, the unmet need for contraception remains high. At the same time, the prevalence of contraceptives has increased in recent years [31]. This study showed an unmet need rate of 26.2% among Senegalese women.…”
Section: Factors Associated With Decision-making Autonomy Among Senegmentioning
confidence: 60%
“…In Senegal, despite numerous health interventions, the unmet need for contraception remains high. At the same time, the prevalence of contraceptives has increased in recent years [31]. This study showed an unmet need rate of 26.2% among Senegalese women.…”
Section: Factors Associated With Decision-making Autonomy Among Senegmentioning
confidence: 60%
“…The other major implication is about reaching out to underserved populations. In a study in Senegal, on “harder to reach” populations, these are defined as “less exposed to external influence and at risk of being underserved despite their high level of need”, and considered to belong to the three categories: adolescents, unmarried and rural poor [ 23 ]. Changing attitudes in communities which are far from everything is a true challenge [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Improving quality of care is a huge challenge requiring substantial financial and programme investments from the Senegalese government and reproductive health partners. Improving access to safe abortion in addition to existing contraception efforts,73 74 and increasing female education, would help prevent higher-risk births and abortion-related mortality.…”
Section: Discussionmentioning
confidence: 99%